Semiconductor/Polymer Nanocomposites of Acrylates and Nanocrystalline Silicon by Laser‐Induced Thermal Polymerization. Issue 11 (21st January 2013) - Deubel, Frank; Steenackers, Marin; Garrido, José A.; Stutzmann, Martin; Jordan, Rainer
Abstract In this work, a novel method for the preparation of polymer/semiconductor nanocomposites is presented. The nanocomposite is directly prepared from a suspension of nanocrystalline silicon (nc‐Si) in bulk vinyl monomers (acrylates) and focused heating of the nc‐Si by irradiation with a pulsed laser at 532 nm wavelength. The silicon nanocrystals are the inorganic component of the composite and simultaneously act as initiation points of the free radical polymerization forming the hybrid composite. By this method, patterned nanocomposite films with thicknesses up to ≈250 µm can be readily prepared. Furthermore, the polymerization kinetics were investigated for different reaction conditions such as irradiation time, laser intensity, nc‐Si content, and addition of radical initiators. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>